Facilitating Team Awareness Through Ambient Displays - Morrison-Smith, Sarah; Chilton, Lydia B.; Ruiz, Jaime (2020)
ABSTRACT Due to the COVID-19 pandemic, research is increasingly conducted remotely without the benefit of informal interactions that help maintain awareness of each collaborator’s work progress. We developed AmbiTeam, an ambient display that shows activity related to the files of a team project, to help collaborations preserve a sense of the team’s involvement while working remotely. We found that using AmbiTeam did have a quantifiable effect on researchers’ perceptions of their collaborators’ project prioritization. We also found that the use of the system motivated researchers to work on their collaborative projects. This effect is known as “the motivational presences of others,” one of the key challenges that make distance work difficult. We discuss how ambient displays can support remote collaborative work by recreating the motivational presence of others. Keywords collaboration, remote work, awareness, ambient display ABOUT THE AUTHOR/S Sarah Morrison-Smith Barnard College smorriso@barnard.edu Lydia B. Chilton Columbia University chilton@cs.columbia.edu Jaime Ruiz University of Florida jaime.ruiz@ufl.edu New Future of Work ’20, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).